Transporting Pesticides and Understanding the Rules of the Road: Farmers, Ranchers and Production Agricultural Operations - Frederick M. Fishel (EDIS, 2008)
PI-160, a 5-page illustrated fact sheet by Frederick M. Fishel, addresses the concern for transporting pesticides that are regarded as hazardous materials by the Secretary of Transportation. This document is specifically written to provide information for those who are considered farmers by the Hazardous Materials Regulations (HMR). Published by the UF Department of Agronomy, January 2008.